Thermo Valve Air Compressor Maintenance and Repair Using the Overall Equipment Effectiveness (OEE) Method in Maintenance - Amalia Ma'rifatul Maghfiroh; Alfian Bima Chandra (Sultan Publisher, 2023)
Production activities carried out every day can interfere with the effectiveness of the machine, one of which is the compressor, so that sometimes problems in the field are still often encountered, such as the piston drive motor not rotating, the compressor does not turn on and off automatically, corrosion (rust), melted capacitors, and many more. things that can happen beyond the operator's control. Due to these constraints, the authors decided to find out more and made direct observations at PT. INKA Multi Solusi Service, as well as studying good and proper machine maintenance so that the company's productivity does not experience a significant decrease. The research was conducted by direct observation and direct interviews with the maintenance department to find out the steps that are usually taken in solving problems. To determine the value of machine effectiveness based on the measurement of three main ratios, namely: availability, performance efficiency, and rate of quality, is carried out using the Overall Equipment Effectiveness (OEE) method. The conclusion that can be drawn from this study is that maintenance on the Ingersoll Rand MM160 type screw air compressor is carried out to maintain the condition of the compressor in a ready state for use in measuring the level of machine effectiveness using the Overall Equipment Effectiveness (OEE) method at PT. IMSS, starting from May – July 2022, where the highest percentage in May 2022 is 94% and the lowest in June 2022 with a percentage is 90%.